Determinants of E-Cigarette Use Among Smokers in Indonesia: An Analysis of Riskesdas and Susenas 2018 - Kadek Rosi Arista Dewi; Putu Ayu Swandewi Astuti; I Wayan Gede Artawan Eka Putra; Ni Made Kurniati (Jurnal Ilmu Kesehatan Masyarakat, 2025)
The increasing popularity of e-cigarettes has emerged as a major public health concern in Indonesia, particularly among youth. This study aimed to identify the determinants of e-cigarette use among Indonesian smokers. A secondary data analysis was conducted using the 2018 Basic Health Research Survey (Riset Kesehatan Dasar, RISKESDAS) and National Socioeconomic Survey (Survei Sosial Ekonomi Nasional, SUSENAS), both cross-sectional national surveys. The sample included 222,373 smokers aged over 10 years selected through total sampling. Variables analyzed comprised socio-demographic and socio-economic factors, alcohol consumption, presence of smoking among family members, and indoor smoking behavior. Logistic regression analysis was performed to identify significant determinant. The prevalence of e-cigarette use among smokers was 2.6%. Significant determinants included age (AOR=16.3; 95% CI=13.6–19.5), education (AOR=1.7; 95% CI=1.5–1.9), employment (AOR=1.4; 95% CI=1.2–1.6), alcohol consumption (AOR=2.1; 95% CI=1.9–2.4), socio-economic status (AOR=1.9; 95% CI=1.6–2.2), smoking among family members (AOR=1.3; 95% CI=1.1–1.6), and indoor smoking (AOR=0.8; 95% CI=0.7–0.9), while gender was not significant. Younger and wealthier smokers were more likely to use e-cigarettes, highlighting the need for targeted regulation and stricter control of advertising, promotion, and access among youth populations.